The first complete mitochondrial genome of Diadema antillarum (Diadematoida, Diadematidae) - Audrey J. Majeske; Alejandro J. Mercado Capote; Aleksey Komissarov; Anna Bogdanova; Nikolaos V. Schizas; Stephanie O. Castro Márquez; Kenneth Hilkert; Walter Wolfsberger; Tarás K. Oleksyk (GigaByte, 2022)
The mitochondrial genome of the long-spined black sea urchin, Diadema antillarum, was sequenced using Illumina next-generation sequencing technology. The complete mitogenome is 15,708 bp in length, containing two rRNA, 22 tRNA and 13 protein-coding genes, plus a noncoding control region of 133 bp. The nucleotide composition is 18.37% G, 23.79% C, 26.84% A and 30.99% T. The A + T bias is 57.84%. Phylogenetic analysis based on 12 complete mitochondrial genomes of sea urchins, including four species of the family Diadematidae, supported familial monophyly; however, the two Diadema species, D. antillarum and D. setosum were not recovered as sister taxa.